Background concentration of airborne microbe in new constructed building - Zainal Abidin, Ahmad Sayuti (2015)
Exposure to indoor air pollution is now becoming serious public health problem in a wide variety of non-industrial setting such as residences, offices, schools, hospital and vehicles. This study investigate the level of airborne microbe in indoor environment at three different phase of building commissioning for a new constructed building in Bandar Baru Bangi, Selangor, Malaysia. Three phases involved is after building devolves to building owner, during installation of furniture and one month after building occupancies. In particular, the airborne microbes’ concentrations were determined by using a single stage impactor (Biosampler) as per requirement of National Institute of Occupational Safety and Health (NIOSH) method, NIOSH Manual Analytical Method NMAM 0800. The total concentration of airborne bacteria were average to 533, 159 and 420 CFU/m3 in the first, second and third phase. For airborne fungi the results yield a mean concentration of 235, 98 and 101CFU/m3 respectively across the sampling phases. These findings indicated that although a new constructed building should be having a significant background level of airborne microbe (total bacteria count and total fungi count). The building owner should be aware to their indoor air status to protect the occupant from the safety and health issue in the work place especially for mechanical ventilated building.